Rice blue beetle incidence in relation to conventional and SRI methods of planting and its correlation with weather parameters - Kakde, A M; Patel1, K G (Indian Journal of Plant Protection, 2020)
An experiment was carried out to study the seasonal incidence of rice blue beetle, Leptispa pygmaea Baly. The study was conducted on two types of rice cultivation systems i.e., conventional planting and system of rice intensification (SRI) method. The results under conventional planting method showed that leaf damage (0.67%) and the population of adults (0.88 adults/plant) first appeared during the last week of July [31st standard meteorological week (SMW)]. It was highest (2.75%) and (2.4/plant), respectively for leaf damage and adult populations on 35th SMW with decline in population from first week of September to last week of September (39th SMW). Under SRI planting method per cent leaf damage (0.69%) and population of adults (0.75 adults/plant) first appeared on (31st SMW) and it gradually increased and reached peak (2.30% leaf damage) and the population of adults (2.31/plant) during the last week of August (35th SMW). It declined from first week of September and was recorded up to last week of September (39th SMW). Thus, blue beetle incidence started from the tillering stage of the crop, increased gradually and reached peak during booting stage of the crop under both the methods of planting. However, SRI method of planting showed less infestation level and the population of rice blue beetle than conventional planting method. The coefficient correlation data revealed that only bright sunshine hours affect the leaf damage and the population of the blue beetle negatively.